2022
DOI: 10.1098/rsbl.2022.0357
|View full text |Cite
|
Sign up to set email alerts
|

Temperature, size and developmental plasticity in birds

Abstract: As temperatures increase, there is growing evidence that species across much of the tree of life are getting smaller. These climate change-driven size reductions are often interpreted as a temporal analogue of the observation that individuals within a species tend to be smaller in the warmer parts of the species' range. For ectotherms, there has been a broad effort to understand the role of developmental plasticity in temperature–size relationships, but in endotherms, this mechanism has received relatively lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 107 publications
0
11
0
Order By: Relevance
“…Disentangling these sources of variation in the context of climate change is particularly challenging, because changing temperature regimes can simultaneously result in altered selection pressures leading to evolution and in systematic differences in developmental environments that trigger plasticity [9]. This important distinction has recently been explored for climate-induced changes in phenology [6,67] and body size [3,9,10], but has not been systematically explored in endocrine flexibility. Better understanding and characterizing variation in endocrine flexibility is a first step in determining when it acts as a facilitator or constraint on coping with climate for both individuals and species.…”
Section: Measuring Flexibility and Sources Of Variation In Flexibilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Disentangling these sources of variation in the context of climate change is particularly challenging, because changing temperature regimes can simultaneously result in altered selection pressures leading to evolution and in systematic differences in developmental environments that trigger plasticity [9]. This important distinction has recently been explored for climate-induced changes in phenology [6,67] and body size [3,9,10], but has not been systematically explored in endocrine flexibility. Better understanding and characterizing variation in endocrine flexibility is a first step in determining when it acts as a facilitator or constraint on coping with climate for both individuals and species.…”
Section: Measuring Flexibility and Sources Of Variation In Flexibilitymentioning
confidence: 99%
“…A growing number of studies have documented the effects of changing temperature regimes on morphology [3,4], behaviour [5,6], species ranges [7] and population stability [8]. These population-wide responses occur through a combination of evolutionary responses to selection and developmental plasticity that are induced, in part, by experiencing a warmer and more variable climate [3,4,9,10]. Understanding these patterns is crucial to predicting the effects of climate change, because evidence has mounted that in many cases populations that are unable to keep pace with climate change are more vulnerable [11] and that particular behaviours, life history strategies, or morphologies predispose some species or populations to increased or decreased capacity to cope with a warming world [12].…”
Section: Introductionmentioning
confidence: 99%
“…For example, in addition to nutrient availability, IGF-1 levels are also very sensitive to temperature. A meta-analysis involving experimentally warmed bird eggs and nestlings revealed that 61% of studies detected a decrease in size related to higher temperatures during development, and suggested changes in IGF-1 signalling resulting from developmental plasticity as a potential mechanism [108]. Interestingly, the effects of temperature can vary depending on both the intensity and duration of exposure.…”
Section: Thyroid Hormonesmentioning
confidence: 99%
“…Interestingly, the effects of temperature can vary depending on both the intensity and duration of exposure. For example, acute exposure to elevated temperatures tends to increase IGF-1 levels and growth and/or feeding rates [16,109], and chronic exposure to elevated temperatures can have opposing effects [108]. Because changes in temperature can also modify metabolic rates and/or resource availability, it will be important to separate the direct effects of temperature acting on the endocrine mechanisms from indirect effects mediated through changes in resource availability [110].…”
Section: Endocrine Mechanisms and Climate Changementioning
confidence: 99%
“…A number of bird species have undergone body size changes during the 20th century. These changes are varied with some species increasing (Kaňuščák et al., 2004; Moreno‐Rueda & Rivas, 2007) but the majority showing a decrease in overall body size (Jakober & Stauber, 2000; Riddell et al., 2019; Weeks et al., 2020, 2022; Yom‐Tov & Yom‐Tov, 2006). This overall decrease, seen not only in birds, has led to some suggesting it is a possible global response to climate change (Daufresne et al., 2009; Gardner et al., 2011; Ryding et al., 2021; Sheridan & Bickford, 2011).…”
Section: Introductionmentioning
confidence: 99%